Analisis Prediksi Kebangkrutan Berdasarkan Metode Z-Score(Studi Kasus pada Perusahaan Semen yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - , Pujiyati; , Lukman Hakim, S.E., M.Si (2017)
This research purpose was to determine the financial health of the cement company that go public the period 2011-2015 and know the early signs of a bankruptcy. Methods of this research used to predict bankruptcy is the Altman Z-Score method that has been equipped with a cut-off point to determine the classification of bankruptcy. Edward I. Altman uses five financial ratios namely Working Capital to Total Assets (X1), Retained Earning to Total Assets (X2), EBIT to Total Assets (X3), Market Value Equity to Book Value of Total Debt (X4) and Sales to Total Assets (X5). Samples of this research used in this study is PT Holcim Indonesia Tbk., PT Indocement Tunggal Prakarsa Tbk. and PT Semen Indonesia (Persero) Tbk. Result of Z-Score calculation PT Holcim Indonesia Tbk. in the years 2011-2015 shows in categories bankrupt. PT Indocement Tunggal Prakarsa Tbk. for five consecutive years healthy condition despite its financial performance fluctuated sometimes increase and sometimes down. PT Semen Indonesia (Persero) Tbk. in the year 2011 showed in the category grey area, in 2012-2014 showed not bankrupt and in 2015 in the category of grey area. Improved management of current needed to overcome the possibility that bad.